The impacts of tobacco control legislation on public view of e-cigarette usage in Macao—The co-word analysis of Macao daily - Chan, Kin-Sun; Xu, Jing; Zhang, Rui; Pang, Patrick Cheong-Iao; Chen, Yu; Zhang, Heng; Liu, Shiyu; Mao, Aimei; Pu, Guanwen; Au, Johnny Ka fai (Frontiers in Communication, 2023)
Introduction Macao has been certified as a “Healthy City” by the World Health Organization, and has been adhering to the principle of combining prevention with proper medical care to build its medical system. As tobacco epidemic is a risk factor leading to a series of non-communicable diseases, the Macao SAR Government has continuously improved tobacco control measures. Methods The data for this study were derived from a news report on “e-cigarettes” published in Macao Daily. Co-word analysis and thematic analysis were conducted to analyze the development of tobacco control legislation against e-cigarettes. Co-word analysis examined the association and frequency of keywords, while thematic analysis identified prevalent themes within the data. Results The study identified three stages of legislation against e-cigarettes: the pre-implementation stage, the early implementation stage, and the epidemic period. Each stage exhibited distinct characteristics and attention toward specific groups, particularly “teenagers” and “students,” increased significantly. Thematic analysis further highlighted the potential issues of drug use and smuggling associated with e-cigarettes. Discussion The findings suggest that the Macao SAR Government should prioritize the development of healthy behaviors among adolescents in the context of e-cigarette control. Additionally, considering regional cooperation to promote the “Healthy Bay Area” could be beneficial. Social media platforms and effective data management should be utilized as tools in these efforts.